THE EFFECT OF LEADERSHIP AND SUPERVISION ON EMPLOYEE DISCIPLINE AT PT. PERKEBUNAN NUSANTARA III (PERSERO) KEBUN BANDAR SELAMAT - Rahmad Bahagia; Siti Sarah; Linzzy Pratami Putri (RADJA PUBLIKA, 2022)
The results of this study have the aim of knowing the existence of